Identification of fluid excitation in pipes - Haqqi, Syed Imad ul Haq (Curtin University, 2016)
Fluid excitation in pipes is identified by modelling turbulence in pipes using Large Eddy Simulation. The results from Computational Fluid Dynamics were coupled with Transient Structural Analysis to perform a one-way Fluid Structure Interaction. Fast Fourier Transforms were performed on the data. This method has identified the difference in the excitation of frequencies in the pipe downstream of a tee junction against those in the pipe downstream of a 90° mitred bend.